Pregnancy after kidney transplantation: when is the best time? - 10.4025/actascihealthsci.v34ispec.10554 - Juliana Barroso Zimmermmann; Hélady Sanders Pinheiro; Alita Eiras Camargo; Anderson Azevedo Andrade; Gustavo Falcão Gama; Alexandre Mitsuo Mituiassu (Universidade Estadual de Maringá, 2012)
The authors report a case of a patient underwent kidney transplantation that went through an unplanned pregnancy, at 41 years old, as well as the implications for both mother and fetus.